Two new species of Tenuipalpus (Acari: Tenuipalpidae) from southeastern Brazil - Mesa, N. C.; de Moraes, G. J.; Ochoa, R. (Zootaxa, 2006)
The flat mites Tenuipalpus isabelae sp. nov. and Tenuipalpus flechtmanni sp. nov. are described based on deutonymphs and adult females collected in Brazil on Actinostemon sp. (Euphorbiaceae) and Campomanesia sp. (Myrtaceae), respectively.